Development of a Worm–Spur Gear-Based Smart Motorised Valve for Intelligent Agricultural Irrigation Systems - Muhamad Hanhan Nugraha; Andy Permana Rusdja; Muhammad Prasha Risfi Silitonga; Anes Inda Rabbika; Ahmad Bustomi; Zezero Meo CA; Risat Dwi Y (Mekanika: Majalah Ilmiah Mekanika, 2026)
Agricultural irrigation systems require precise, effective, and efficient automatic valves; however, in practice, most of the technology used remains relatively simple, often leading to torque problems, leaks, and control limitations. This research aims to design an SDGMOV based on a worm-spur gear transmission and integrated with an IoT control system to support agricultural water regulation. The research methods include torque measurement using digital scales, CAD design and 3D printing with PLA, calculation of valve hydrostatic pressure, and force analysis using FEA. The control system was developed using an ESP32 microcontroller connected to a mobile application to enable remote monitoring and operation. The study’s results showed that the torque requirement of 1.62 N.m could be safely met by a servo motor that has a torque of 3.43 N.m. At the same time, FEA analysis of the bracket and cover revealed that the stress levels remained below the material’s permitted stress, with a FOS value exceeding 1.5. Additionally, the hydrostatic pressure calculation was significantly lower than the material’s strength, ensuring its safety for use. The implementation of the ESP32-based control system ensures stable, precise remote operation, enabling the SDGMOV design to enhance the precision, efficiency, and reliability of water distribution.